Random Undersampling on Imbalance Time Series Data for Anomaly Detection - Saripuddin M.; Suliman A.; Syarmila Sameon S.; Jorgensen B.N. (Association for Computing Machinery, 2023)
Deep learning; Learning algorithms; Time series; Anomaly detection; Electricity theft detection; Imbalance datum; Imbalance time series data; Over sampling; Overfitting; Random under samplings; Resampling approaches; Time-series data; Under-sampling; Anomaly detection